Identification of a second locus in Drosophila melanogaster required for excision repair. - Boyd, J.B.; Snyder, R.D.; Harris, P.V.; Presley, J.M.; Boyd, S.F.; Smith, P.D. (Genetics, 1982)
The mus(2)201 locus in Drosophila is defined by two mutant alleles that render homozygous larvae hypersensitive to mutagens. Both alleles confer strong in vivo somatic sensitivity to treatment by methyl methanesulfonate, nitrogen mustard and ultraviolet radiation but only weak hypersensitivity to X-irradiation. Unlike the excision-defective mei-9 mutants identified in previous studies, the mus(2)201 mutants do not affect female fertility and do not appear to influence recombination proficiency or chromosome segregation in female meiocytes.--Three independent biochemical assays reveal that cell cultures derived from embryos homozygous for the mus(2)D1 allele are devoid of detectable excision repair. 1. Such cells quantitatively retain pyrimidine dimers in their DNA for 24 hr following UV exposure. 2. No measurable unscheduled DNA synthesis is induced in mutant cultures by UV treatment. 3. Single-strand DNA breaks, which are associated with normal excision repair after treatment with either UV or N-acetoxy-N-acetyl-2-aminofluorene, are much reduced in these cultures. Mutant cells possess a normal capacity for postreplication repair and the repair of single-strand breaks induced by X-rays.